2022
DOI: 10.3389/fnins.2022.937145
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Dynamic Functional Connectivity of Posterior Cingulate Cortex Subregions in Major Depressive Disorder With Suicidal Ideation

Abstract: Accumulating evidence indicates the presence of structural and functional abnormalities of the posterior cingulate cortex (PCC) in patients with major depressive disorder (MDD) with suicidal ideation (SI). Nevertheless, the subregional-level dynamic functional connectivity (dFC) of the PCC has not been investigated in MDD with SI. We therefore sought to investigate the presence of aberrant dFC variability in PCC subregions in MDD patients with SI. We analyzed resting-state functional magnetic resonance imaging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 68 publications
(85 reference statements)
0
3
0
Order By: Relevance
“…Phillippi et al found that severity of depression in patients with StD was associated with reduced connectivity between pregenual anterior cingulate cortex (pgACC) and the striatum, as well as reduced connectivity between anterior subgenual anterior cingulate cortex (sgACC) and the anterior insula ( Philippi et al, 2015 ). The posterior cingulate, a key part of the DMN, is a critical hub for self-referential processing, cognitive control and emotion processing, and serves as a cortex underlying multidomain cognitive function through its connections to distal cortical areas ( Li et al, 2022 ). Dotson et al found that patients with StD exhibited reduced cortical thickness in the right posterior cingulate gyrus, compared to the left posterior cingulate gyrus, and this change was associated with more severe somatic symptoms of depression ( Dotson et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Phillippi et al found that severity of depression in patients with StD was associated with reduced connectivity between pregenual anterior cingulate cortex (pgACC) and the striatum, as well as reduced connectivity between anterior subgenual anterior cingulate cortex (sgACC) and the anterior insula ( Philippi et al, 2015 ). The posterior cingulate, a key part of the DMN, is a critical hub for self-referential processing, cognitive control and emotion processing, and serves as a cortex underlying multidomain cognitive function through its connections to distal cortical areas ( Li et al, 2022 ). Dotson et al found that patients with StD exhibited reduced cortical thickness in the right posterior cingulate gyrus, compared to the left posterior cingulate gyrus, and this change was associated with more severe somatic symptoms of depression ( Dotson et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, victimization was richly associated with functional connectivities between several neurocognitive networks (e.g., DMN, DAN, VAN), which might serve as a common biomarker for vulnerability to mental disorders [ 73 75 ]. Accumulating evidence reveals the association of suicide with the structural and functional abnormalities of the PCC, forming a key hub for cognitive control and serving as a crucial part of the DMN [ 76 78 ]. Indeed, as shown in previous research, DMN has been considered to play an important role in episodic retrieval, regulating internally directed cognition (e.g., future imaging events), and self-referential processing [ 79 , 78 , 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a recent study of Li et al (2022a) is very timely. In their study, the authors supposed that (1) MDD with SI would show aberrant dFC variability in PCC subregions as compared with MDD without SI and HCs; and (2) the anomalous dFC variability would exhibit associations with clinical variables.…”
mentioning
confidence: 99%